2‐fluoro‐5‐maleimidobenzoic acid‐linked albumin drug (MAD) delivery for selective systemic targeting of metastatic prostate cancer. Issue 9 (24th March 2018) - Akinboye, Emmanuel S.; Rogers, Oliver C.; Isaacs, John T.
Abstract : Background: The SH‐group at Cys‐34 of human serum albumin (HSA) is a unique and accessible functional group that can be exploited for efficient linkage of a maleimide containing cytotoxic drug derivative to albumin. The specific maleimide chemistry used for production of the maleimide‐linked albumin drug (MAD) is critical, however, to minimize the plasma concentration of "free" cytotoxic drug spontaneously released from albumin carrier thus decreasing dose‐limiting host toxicity while enhancing the plasma half‐life from minutes to days (ie, pharmacokinetic effect) and tissue concentration of the MAD in the extracellular cellular fluid at sites of cancer (ie, EPR effect). Methods: To accomplish this goal, a chemical synthesis was developed using 2‐fluoro‐5‐maleimidobenzoic acid to stably link the potent cytotoxic chemically modified analogue of the naturally occurring sesquiterpene γ‐lactone, thapsigargin, 8‐O‐(12‐aminododecanoyl)‐8‐O‐debutanoyl thapsigargin (12ADT), to Cys‐34 of albumin to produce 12ADT‐MAD. Results: Using FITC‐labeling, LC/MS analysis, and in vitro growth and clonogenic survival assays on a series of 6 human prostate cancer lines (LNCaP, LAPC‐4, VCap, CWR22Rv 1, PC3, and Du145), we documented that 12ADT‐MAD is endocytosed by prostate cancer cells where it is degraded into its amino acids liberating cysteinyl‐maleimide‐12ADT which is both chemically stable at the acidic pH of 5.5 present in the endosome while retaining its high killing ability (IC50 50 nM) via SERCA inhibition. Conclusions: Based upon these positive in vitro validation results, the in vivo efficacy versus host toxicity of this 12‐ADT‐MAD approach is presently being evaluated against a series of patient derived androgen responsive and castration resistant human xenografts in immune‐deficient mice.